Creatine as an ergogenic aid for female athletes. - Eckerson, J. M. (Strength and Conditioning Journal, 2016)
Creatine (cr) is an effective ergogenic aid for female athletes, but may be overlooked because of a perception that it causes weight gain. Studies using women show that both short-term and long-term cr supplementation enhances muscular strength and power and other measures of anaerobic and aerobic exercise performance with minimal effects on body composition. Therefore, female athletes involved in sports that require a low body weight, aesthetically judged sports, and weight-class sports may find cr to be a useful dietary supplement. The current review summarizes research findings that used women as subjects and provides guidelines for supplementation.